Simulation of DC Motor Control Systems Using SISO, SIMO, MISO, and MIMO Configurations with LQR and LQT Control for Sustainable Community - Muhamad Rifqi Anugrah Syafa’at; Rama Arya Sobhita (Maritime in Community Service and Empowerment, 2025)
Electric motors are devices that convert electrical energy into mechanical energy. In a DC motor, this energy conversion occurs as a current flows through a coil in the stator, causing the rotor to rotate due to magnetic field repulsion. This research focuses on the application of DC motors in community service projects, particularly in systems that support sustainable development efforts in rural and underdeveloped areas. In such settings, DC motors are often used in various community development projects, including water pumping systems, small-scale energy generation, and agricultural machinery. The ease of controlling DC motors, particularly through advanced control systems, makes them ideal for these applications. This study investigates the impact of different control strategies on the performance of DC motors, specifically comparing SISO (Single Input, Single Output), SIMO (Single Input, Multiple Output), MISO (Multiple Input, Single Output), and MIMO (Multiple Input, Multiple Output) systems. Each of these systems offers unique advantages for controlling the motor's performance, such as optimizing speed, torque, and energy efficiency, which are critical in real-world community applications. The simulation results will provide insights into the advantages of each control system and highlight how these can improve the overall efficiency and reliability of systems that directly impact community welfare. The findings from this study are expected to be highly relevant for community service applications, offering practical solutions for enhancing the quality of life through better-designed technologies and optimized systems.